For a Wider World : Sixty Works in the British Council Collection. - Francis, Richard; The British Council (London : the British Council, 1990)
Moore, Henry ; Sutherland, Graham ; Nash, Paul ; Nicholson, Ben ; Freud, Lucian ; Lanyon, Peter ; Hilton, Roger ; Paolozzi, Eduardo ; Armitage, Kenneth ; Hockney, David ; King, Philip ; Caulfield, Patrick ; etc.
Engels
boek